Failure analysis of a new-type shield tunnel based on distributed optical fiber sensing technology. (December 2022) - Zhang, Junchen; Yan, Qixiang; Li, Weiping; Su, Liufeng; Sun, Minghui; Yao, Chaofan
Highlights: The prototype experiment was carried out based on a new-type shield tunnel. The mechanical behavior of segmental joint was studied using optical fiber sensor. The failure characteristics of the joint with the assembled dowel were revealed. Abstract: The dislocation of circumferential joints in shield tunnel has serious safety impact on subway operation. A new-type shield tunnel with dowel was used to limit the dislocation of circumferential joints of the tunnel in Chengdu Metro. In this paper, the prototype segmental experiment is carried out to analyze the shear performance of circumferential joint of tunnel with the dowel. The optical fiber sensing technology is used to investigate the deformation characteristics and crack propagation law of concrete. And the change laws of the dowel, bolt and rebars in segment are obtained in detail. The research shows that segments with the assembled dowel have its particular failure mode in the shear process. The dowel significantly changes the stress of concrete, bolt and rebars. The research results provide a theoretical basis for the application and promotion of the new segment structure.